2021
DOI: 10.47389/36.3.78
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary behavioural health issues associated with disaster response

Abstract: Emergencies and disasters create stressful situations that can exacerbate ongoing behavioural health issues. Veterinarians have been identified as a professional group at elevated risk for behavioural health issues when they are involved with an emergency response. Prior studies looking at transboundary animal disease disaster management demonstrate the significant and long-lasting mental health effects experienced by veterinary responders. To examine the scale and scope of behavioural health issues exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The current study found a significant relationship between depopulation involvement and burnout, with higher levels of burnout reported by those involved in the depopulation effort. Previous studies have noted the negative psychological impact of participating in depopulation efforts, including a recent analysis by Vroegindewey ( 75 ), who reported that 50% of respondents reported immediate behavioral health issues and 32% reported still having symptoms six months after deployment. Furthermore, the depopulation method had a significant impact on burnout and depopulation distress in the form of Ethics of Care and Perception of Others.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found a significant relationship between depopulation involvement and burnout, with higher levels of burnout reported by those involved in the depopulation effort. Previous studies have noted the negative psychological impact of participating in depopulation efforts, including a recent analysis by Vroegindewey ( 75 ), who reported that 50% of respondents reported immediate behavioral health issues and 32% reported still having symptoms six months after deployment. Furthermore, the depopulation method had a significant impact on burnout and depopulation distress in the form of Ethics of Care and Perception of Others.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a preparedness plan can help to build emotional readiness and resilience. 35 As leaders in the community, trained veterinary professionals can substantially impact community-wide efforts to respond appropriately to animal cruelty.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] However, most investigations into how VACWs experience disasters have focused on veterinarians responding to disease outbreaks. 8 Less empirical evidence exists on the experiences of VACWs exposed to other types of disasters, including natural hazards. Additionally, the literature largely ignores VACWs who collaborate with veterinarians during disasters.…”
Section: The Current Studymentioning
confidence: 99%
“…7 There has been little investigation into the potential repercussions for VACWs who conducted this work during the Black Summer, although there is evidence that veterinarians have experienced psychological adversity associated with previous disasters globally. 8 VACWs affected by the Black Summer bushfires may be similarly susceptible to poor mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation